Review of S&T policy plans in ACP countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
In 2003, Louk Box and his team at the University of Maastricht in the Netherlands reviewed 52 S&T plans for ACP countries.